SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN (SKMHT) YANG DIBUAT DENGAN AKTA NOTARIS BERDASARKAN PASAL 96 AYAT (1) PERKABAN NO. 8 TAHUN 2012 DIKAITKAN DENGAN PASAL 38 UUJN NO. 30 TAHUN 2004 DALAM MELINDUNGI HAK KREDITOR - AULIA RACHMAN AMIRTIN (PREMISE LAW JURNAL, 2015)
The result of this study showed that the SKMHT made under the Notarial deed which should be regulated and object to Article 38 of Law No. No.30/2004 (UUJN) was not realized because the SKMHT was made based on Article 96 paragraph (1) of the Regulation of the Head of Land Board. This was done because if the SKMHT was not made based on Article 96 paragraph (1) of the Regulation of the Head of Land Board, the SKMHT was not accepted during the process of Collateral Right registration in the Office of National Land Board (BPN). The power of proving the SKMHT made under the Notarial deed based on Article 96 paragraph (1) of the Regulation of the Head of Land Board and related it to the stipulation of authentic deed based on Article 1868 and Article 1888 of the Indonesian Civil Codes showed that the SKMHT does not meet any criteria of authentic deed, but it is ignored by either Notary/ Land Certificate Issuing Officer, National Land Board, or even the bank as the interested parties to the SKMHT deed.  The SKMHT deed is in fact does not have an executorial power on the land/the collateral object that it has no power in protecting the right of creditor. Therefore, it is necessary to continue the APHT and the issuance of Collateral Right Certificate which has the executorial power and provides the right of preference to the creditor as the Collateral Right holder. Keywords: Power of Attorney Imposing Collateral Right